The Impact of Rewards and Punishments on Enforcing Santris' Discipline at Dayah Terpadu Jami'ah Azzanjabil - Iqbal, Muhammad; Najmuddin, Najmuddin; Syafawi, Qamar (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2024)
Discipline is one of the important ways to succedd. Dayah Integrated Jami'ah Azzanjabil alumni bind their students with strong discipline to achieve success. Many students violate Dayah's rules, even though it has implemented the rules and even gives rewards to students who excel and punishment to students who violate student discipline. This is the background of the problem that motivates researchers to conduct this topic. It aims to determine the mechanisms and obstacles to enforcing student discipline regarding the provision of rewards and punishments at Dayah Terpadu Jami'ah Azzanjabil. It employed qualitative research. This research wa conducted at Dayah Terpadu Jami'ah Azzanjabil, located in Buket Teukueh Village, Kota Juang District, Bireun Regency, Aceh Province. Data collection techniques were obtained through observation, interviews, and documentation. The data analysis method used in this research was the descriptive data analysis method. It included the preparation stage, data grouping stage, and conclusion. It is found that the mechanism for enforcing student discipline regarding the provision of rewards and punishment in Dayah Terpadu Jami'ah Azzanjabil is, Firstly, by implementing discipline by starting with force until the students get used to carrying out the discipline until they finally enjoy the existing discipline. Second, Form the Dayah Azzanjabil Santri Organization (OSDA) administrators and guide them in preparing programs to help carry out discipline in the Integrated Dayah Jami'ah Azzanjabil with the help of their monitoring. The conclusion of this research is to apply discipline by starting with force until the students get used to carrying out the discipline until they finally enjoy the existing discipline, forming administrators of the Dayah Azzanjabil Santri Organization (OSDA), enforcing disciplines such as worship, time, study, practice, cleanliness, and kindness.